Peningkatan Polymorphonuclear (PMN) Dalam Cairan Nasal Lavage Operator Penggilingan Padi Yang Terpajan Endotoksin Lipopolisakarida (LPS) - William Wilfridus Lamawuran (JURNAL INFO KESEHATAN, 2018)
Background: Exposure to lipopolysaccharide endotoxin (LPS) in rice dust causes respiratory inflammation which is characterized by an increase in Neutrophils or Polymorphonuclear (PMN) in the nasal lavage fluid of rice milling operators. Objective: The purpose of this study was to analyze the effect of endotoxin LPS on the rice mill operators' PM in the rice level operators. Methods: the design of this study was a longitudinal study. Dust sampling was carried out for 8 hours while nasal lavage samples were carried out before and after work (cross shift). Endotoxin PMN and LPS were analyzed using the ELISA method and LPS Endotoxin was analyzed using LAL. Results: The mean level of LPS endotoxin in rice dust was 56.36 ± 5.83 EU / m3. An increase in post-employment PMN (Pired sample t-test: p = 0.000) in all rice milling operators. LPS endotoxin levels correlated with increased PMN in nasal lavage fluid in rice milling operators (multiple linear regression test: p = 0.000). Conclusion: LPS endotoxin is a factor that influences the increase of PMN levels in nasal lavage fluid which indicates the occurrence of inflammation in rice mill operators. Suggestion: Use a rice milling machine equipped with a dust collector. Health checks are given to the rest of their work. Workers are advised to always use masks while working.